MENGGALI EFEKTIFITAS KOMUNIKASI PEMASARAN OBJEK WISATA KOTA PADANG MELALUI INSTAGRAM - Afifah Afifah; Ranti Komala Dewi; Yosi Suryani (Jurnal Pariwisata Pesona, 2019)
Advertising acts as a medium that will introduce a product or service provide an explanation of the benefits and attract someone to consume it. Nowadays advertisements can be displayed in print and electronic media. Businesses, non-profit organizations and even government agencies use almost all types of media to advertise. Padang City Tourism Office as a government agency that deals with Padang City tourism uses electronic media in promoting the attractions of Padang City. Promotional media used are Instagram, advertising media based on social media applications. This article aims to investigate whether the advertisements or information provided by Instagram has been effective. The effectiveness evaluation of the Instagram uses the EPIC Model approach which consists of four variable dimensions: (1) Empathy, (2) Persuasion, (3) Impact and (4) Communication. The four dimensions were analyzed through answers obtained through a survey of 120 respondents. From the analysis done, it can be seen that Instagram in general can be categorized as an effective promotional media. But there are still a few things that need to be considered so that the effectiveness of this media achieves maximum quality, namely: (1) The completeness and updating of the information presented must be maintained in order to attract empathy from the connoisseurs of advertising; (2) creativity in compiling ad content needs to be developed in order to appear happy feelings and desires to become followers of the Instagram account; (3) Instagram should have its own communication style such as creating an interesting narration to accompany a photo or video so as to create a deep impression for ad lovers.